The Effect of Financial Performance to Share Returns on Companies IDX 30 Indexed During The Covid Pandemic at The Indonesian Stock Exchange - Nurhayati, Nurhayati; Marviana, Ratna Dina; Rangkuti, Sahnan (Ekonomis: Journal of Economics and Business, 2024)
This research is a replication of several previous on going studies due to previous research results that tried to test the influence of financial performance on stock returns on IDX 30 during the covid 19 pandemic. The study is intended to obtain an explanation of empirical facts on the influence of factors described through financial stability, external pressure, and financial targets together and partial influences financial statement fraud on banking companies during the period of COVID 19 on the Indonesian Stock Exchange. The population in this study is all IDX 30 indexed companies on the Indonesian Stock Exchange, namely as many as 30 companies. With sample count of 22 companies. The type of data used in this study was secondary data with the amount of observation from 2019-2020 during the COVID 19 pandemic period so that it became a sample of observation of 22 X 2 = 44 samples, and the scale used in this study was the scale of ratio and analysis of data used was with the multiple linear regression approach at a significant rate of 5%. Research will be very useful input for investors as an important guideline for looking at the condition of the company and the fundamental aspects to assess the expectations of the return (return shares) that it will acquire and as a decision maker to buynot buy shares of the company. The results of this research are also expected to be used by IDX 30 companies to find out their condition and finances so as to improve the financial performance of the next period that will eventually affect the company’s stock price. In addition, this research can also be used as the basis for advanced research to review financial performance viewed from different perspectives of financial instruments.